Caracteriza??o do canal de comunica??o em redes de distribui??o de energia el?trica de baixa tens?o - Vital, Richard Brand?o Nogueira (2010)
In this dissertation we present the results of a study about the characterization of the low-voltage powerline communication (PLC) channel used in powerline com- munication systems. Besides the theoretical approach, we also present real mea- surements from a given indoor PLC channel as a case study. These measurements include frequency response, impulse response, group delay, coherence bandwidth, time dispersion and noise behavior. We also report how these measurements can be analyzed from the perspective of their statistical characteristics.